A hybrid game with conditional and unconditional veto power - Werner Güth; M. Vittoria Levati; Natalia Montinari; Chiara Nardi (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2014)
In the hybrid game, one proposer confronts two responders with veto power: one responder can condition his decisions on his own offer but the other cannot. We vary what the informed responder knows about the offers as well as the uninformed responders conflict payoff. Neither variation affects behavior: proposers always favor informed responders, who frequently accept minimal offers.
Keywords: C72; C92; 330; Ultimatum; Yes/No game